Optimalisasi Biaya dan Waktu Pelaksanaan Proyek Pembangunan dengan Metode PERT-CPM - sari maryani; dewi murni (UNIVERSITAS NEGERI PADANG, 2019)
Abstract— Project is a combination of several resources such as capital / costs, human, material and equipment in a temporary organization that aims to achieve certain goals.Estimating the duration and improper costs at this step will affect the implementation of activities and the results obtained. This researchpurpose to optimize the duration and cost of implementing the PLUT-KUMKM development project in Sumatra Barat with PERT-CPM method then followed by crashing. This research uses data on project activities, the sequence and cost of each activity. The results of this research can optimize the project implementation time with almost the same cost, from 21 weeks become 18 weeks. It means thatthe project implementation time can be accelerated by 14,3 % of the initial duration. With project implementation cost Rp.1.724.873.973,93 to Rp.1,787,703,844.13.Keywords—Project, PERT-CPM, crashing